Early Childhood Education Intervention Programs in the Netherlands: Still Searching for Empirical Evidence - Geert Driessen (MDPI AG, 2017)
Early childhood education (ECE) intervention programs nowadays are the core of the educational disadvantage policy in the Netherlands. They offer institutional compensatory activities to young children who lack educational stimulation in the home environment. Target groups mainly comprise children from deprived socioeconomic backgrounds and of immigrant origin. ECE is confronted with several bottlenecks, including the definition of the target groups, the quality of ECE staff, and the ECE programs. Most important is the controversy surrounding the empirical evidence of effects of ECE provisions. This article presents a description of state-of-the-art Dutch ECE, with special attention to recent Dutch studies on the effectiveness of ECE programs.